P277 A new pan enteric capsule for suspected or established IBD: A feasibility study assessing the system functionality to visualise and assess the small and large bowels. (16th January 2018) - Eliakim, R; Spada, C; Fernandez-Urien Sainz, I; Yanai, H; Lahat, A; Ron, Y; Pecere, S; Costamagna, G; Schwartz, A; Eyal, I; Lapidus, A; Adler, S
Abstract: Background: Inflammatory bowel disease (IBDs) requires evaluation of the gastrointestinal (GI) tract to assess disease extent and severity. The PillCam Crohn's system is a new system composed of a two-headed capsule with a panoramic field of view and adaptive frame rate, customised for extensive coverage of the GI tract, to assess and follow disease severity and extent over time. The aim of this study was to assess system functionality in suspected or established IBD patients. Methods: A feasibility study was performed prospectively in 5 different centres. Study subjects ingested the new PillCam™ Crohn's capsule after standard bowel preparation plus boosts. A patency capsule was ingested first to ensure adequate patency of the GI tract prior to capsule. The primary study endpoint was successful procedure in terms of video creation and report generation in accordance to the video reading methodology. Secondary study endpoints were subjective coverage of small bowel and colon (SBC), subjective duration of total and segmental reading time, over all video quality and occurrence/ severity of adverse events. Results: 68 patients were screened, 54 enrolled, and 49 ingested the capsule (14 patency failure (21%), 5 withdrew consent). Forty-one patients were included in the final analysis and had no procedure-related deviations (bowel preparation materials and boosts consumption). Mean age was 40.8 years ± 15.5 (mean ± standard deviation), 46% were males. 71% of patients had established CD, 12% UC and 17% suspected CD. The disease was active in 54% of established IBD patients. Overall cleansing was regarded good or excellent in 95% of patients. All 41 videos met the primary endpoint. All capsules reached the left colon/toilet with no retention, 95% while recording. Of those with established CD, 31% had proximal disease. Gastroenterologists were satisfied with SBC coverage 6.7 ± 0.6 and 6.1 ± 1.3 (mean ± standard deviation) on a scale of 1–7 (unconfident to confident), image quality 6.1 ± 0.8 (1–7, poor to excellent), and subjective video reading time 3.7 ± 1.4 (1–7, very short to very long). Conclusions: The PillCam™ Crohn's capsule allows for extensive evaluation of the entire gut of IBD patients, including those with proximal disease. The system can be used to assess disease severity, extent, and follow-up of IBD patients.